Identification of Functional Interactome of Colistin Resistance Protein MCR-1 in Escherichia coli - Li, Hui; Wang, Yingyu; Chen, Qiyan; Xia, Xi; Shen, Jianzhong; Wang, Yang; Shao, Bing (Frontiers in Microbiology, 2021)
The emergence and worldwide dissemination of plasmid-mediated colistin resistance gene mcr-1 has attracted global attention. The MCR-1 enzyme mediated colistin resistance by catalyzing phosphoethanolamine (PEA) transfer onto bacterial lipid A. However, the interaction partners of MCR-1 located in membrane protein in E. coli are unknown. Co-immunoprecipitation (Co-IP) and Mass Spectrometry were performed to define the interacting proteins of MCR-1. A total of three different anti-MCR-1 monoclonal antibody (mAbs) were prepared and 3G4 mAb was selected as the bait protein by compared their suitability for Co-IP. We identified 53, 13, and 14 interacting proteins in E. coli BL21 (DE3) (pET28a-mcr-1), E. coli BL21 (DE3) (pET28a-mcr-1-200), and E. coli DH5α (pUC19-mcr-1), respectively. Six proteins, including the stress response proteins DnaK (chaperone protein) and SspB (stringent starvation protein B), the transcriptional regulation protein H-NS, and ribosomal proteins (RpsE, RpsJ, and RpsP) were identified in all these three strains. These MCR-1-interacting proteins were mainly involved in ribosome and RNA degradation, suggesting that MCR-1 influences the protein biosynthesis through the interaction with ribosomal protein. Multidrug efflux pump AcrA and TolC were important interacting membrane proteins of MCR-1 referred to drug efflux during the PEA modification of the bacterial cell membrane. Overall, we firstly identified the functional interactome profile of MCR-1 in E. coli and discovered that two-component AcrA-TolC multidrug efflux pump was involved in mcr-1-mediated colistin resistance.